Penggunaan Alat Peraga pada Mata Pelajaran IPA Fisika tentang Bunti Di Sekolah Dasar - Alvi Syafaatu Rosidah; Asyahidah Alqurni; Muhammad Suwigno Prayogo (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The purpose of this study was to describe the use of visual aids in the science subject Physics about sound in elementary schools. This study used a qualitative approach using the library research method, data collection techniques using observation (text study), and documentation. In the data analysis technique, the researcher used Source Triangulation. The results showed that students' learning motivation had a significant effect on science learning outcomes. Online learning and learning motivation simultaneously contribute 15.9% to the learning outcomes of fourth-grade students in elementary schools. In addition, there is a positive correlation between students' learning motivation and science learning achievement, with the magnitude of the correlation at a significant level.